Development and Validity Testing of a Morning Stiffness Assessment Scale for Patients with Rheumatoid Arthritis. (January 2021) - Oh, HyunSoo; Bang, SuHyang; Im, BoAe; Lee, SiWon; Seo, WhaSook
Abstract : Morning stiffness is known to exert a significant impact on functional ability, quality of life, and employment status. There is an increasing need for a valid, reliable tool to comprehensively assess morning stiffness. The purpose of this study was to develop and verify a Morning Stiffness Assessment Scale. Items were developed on the basis of a framework of the conceptual attributes of morning stiffness. Validity and reliability tests were conducted on the devised scale. Eighty-five patients with rheumatoid arthritis were included to verify the devised scale. A 10-item Morning Stiffness Assessment Scale was developed. Its content and construct validities were well supported. The scale was found to have good reliability. The devised scale is simple and brief, but it provides a more comprehensive means of evaluation for morning stiffness. We believe this scale offers a clinically useful means of properly assessing morning stiffness and has potential utility for evaluating the effects of morning stiffness treatments.